Studi Pendahuluan Perubahan Garis Pantai Selama Zaman Kuarter di Daerah Kroya sampai Binangun Kabupaten Cilacap-Jawa Tengah - Widagdo, Asmoro; Setijadi, Rachmad (Jenderal Soedirman University, 2013)
Cilacap coast line is a part of southern coast of Java at Cilacap Regency, Central Java. Topographic and satellite image observation shown some ancient coast lines behind the modern coast lines. How many of the coast lines which have formed before the modern coast lines is the question to be answered. This research is the preliminary effort to determine the direction of coast line development and the amount of coast lines which have formed before the modern ones. This preliminary research of the ancient coast lines is done by two stages of work that are studio and field work. Studio work was done by observation and interpretation of topographic map, land use map, Google Earth image and SRTM image. At this stage of work was made an ancient coast lineaments map and geomorphic profiles of the research area. To the results of the interpretation which have been done then taken a field work verification by ground check. Interpretation to the coast lines of the research area has resulted 24 coast lines. Ancient coast lines lineament of the research area is in line with the modern ones which have east-west lineament and prograde from the north to southward.